The Effectiveness of Using Augmented Reality Technology in Developing Cognitive Achievement and the attitudes Towards Information Technology for Eighth grade Female Students of Basic Education in the Sultanate of Oman (Journal Of Educational and Psychological Researches, 2025)
The research aims to investigate the effectiveness of using augmented reality technology in enhancing cognitive achievement and attitudes toward information technology among eighth-grade female students. The experimental approach was employed. The research sample consisted of 42 students from Al-Mazyouna Basic Education School (Grades 5-12) in the Dhofar Governorate, Oman; students were divided into two groups: an experimental group and a control group. The research utilized an achievement test to measure cognitive achievement and a scale to assess attitudes toward learning information technology. The results revealed that there are statistically significant differences between the two groups in terms of cognitive achievement and attitudes toward information technology, in favor of the experimental group. The research recommended training teachers and supervisors in utilizing augmented reality technology to enhance students' academic performance and foster positive attitudes towards the subject.